11.2k views
3 votes
-2(y + 1) + 5y = 3(y + 1) - 2
solve for y

User Jossue
by
6.5k points

1 Answer

5 votes

Answer:

0 = 3 or No Solution

Explanation:

a) Simplify both sides of the equation

−2(y + 1) + 5y = 3(y + 1) − 2

(−2)(y) + (−2)(1) + 5y = (3)(y) + (3)(1) + −2

−2y + −2 + 5y = 3y + 3 + −2

(−2y + 5y) + (−2) = (3y) + (3 + −2)

3y + −2 = 3y + 1

3y −2 = 3y + 1

b) Subtract 3y from both sides

3y − 2 − 3y = 3y + 1 − 3y

−2 = 1

c) Add 2 to both sides

−2 + 2 = 1 + 2

0 = 3 or No Solution

User Ender Che
by
6.2k points